Respuesta :
I will assume that everything after the radical sign is under the sign...
6√(64x^4y^2)
6√(8^2(x^2)^2(y^2)) removing all of the perfect squares...
6*8*x^2*y
48x^2y
6√(64x^4y^2)
6√(8^2(x^2)^2(y^2)) removing all of the perfect squares...
6*8*x^2*y
48x^2y
[tex]6 \sqrt{64x^4y^2}=6 \sqrt{8^2} \sqrt{(x^2)^2} \sqrt{y^2} =6*8x^2y=48x^2y [/tex]
Edited:
[tex] \sqrt[6]{64x^4y^2}= \sqrt[6]{2^6x^4y^2}= 2 \sqrt[6]{x^4y^2} [/tex]
Edited:
[tex] \sqrt[6]{64x^4y^2}= \sqrt[6]{2^6x^4y^2}= 2 \sqrt[6]{x^4y^2} [/tex]